2014
DOI: 10.1128/iai.01271-13
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphoenolpyruvate Phosphotransferase System in Group A Streptococcus Acts To Reduce Streptolysin S Activity and Lesion Severity during Soft Tissue Infection

Abstract: bObtaining essential nutrients, such as carbohydrates, is an important process for bacterial pathogens to successfully colonize host tissues. The phosphoenolpyruvate phosphotransferase system (PTS) is the primary mechanism by which bacteria transport sugars and sense the carbon state of the cell. The group A streptococcus (GAS) is a fastidious microorganism that has adapted to a variety of niches in the human body to elicit a wide array of diseases. A ⌬ptsI mutant (enzyme I [EI] deficient) generated in three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 62 publications
(75 reference statements)
3
47
0
Order By: Relevance
“…Our previous work showed that a PTS null mutant (Δ ptsI ) in the M1T1 GAS strain MGAS5005 resulted in an increased size and severity of lesions at the site of infection in a murine soft tissue infection model due to the early onset of expression and activity of Streptolysin S (SLS) during growth (Gera et al , 2014). However, the contribution of individual sugar-specific EII components in this link to virulence was not explored.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work showed that a PTS null mutant (Δ ptsI ) in the M1T1 GAS strain MGAS5005 resulted in an increased size and severity of lesions at the site of infection in a murine soft tissue infection model due to the early onset of expression and activity of Streptolysin S (SLS) during growth (Gera et al , 2014). However, the contribution of individual sugar-specific EII components in this link to virulence was not explored.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative mechanism of CCR in bacteria is known as induction prevention, which is dependent on the sugar phosphotransferase (PTS) system and the phosphorylation state of a conserved histidine residue of the phosphocarrier protein HPr (36), which in the case of S. pyogenes is His15 (39). If the ME loci are controlled by a mechanism similar to induction prevention, then cells unable to produce phosphorylated His-HPr (PϳHis-HPr) should be unable to utilize malate.…”
Section: Me Is Necessary For S Pyogenes Malate-enhanced Growthmentioning
confidence: 99%
“…Taken together, these data suggest that fruA is required for optimal growth on fructose and that FruA is the main fructose transporter for GAS. Since a PTS-defective mutant (⌬ptsI) of M1T1 GAS is defective for the utilization of fructose in the Biolog assay (12), there appears to be another PTS EII that is able to transport fructose to be metabolized, albeit not at the levels necessary to support GAS growth on fructose. Finally, the loss of fruA affects the utilization of other carbon sources; however, this is unsurprising, because a ⌬ptsI mutant also affects the utilization of non-PTS carbon sources through currently unknown mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…GAS disease progression is heavily dependent on the ability of GAS to coordinate its environmental cues and nutritional status with global transcriptional networks. Examples of such synchronization include the stand-alone regulator Mga, whose activity is directly affected by the PTS (7), LacD.1, the tagatose-1,6-bisphosphate aldolase that acts as an inhibitor of speB transcription (8), and CcpA and EI (ptsI), which both indirectly repress the expression of the hemolysin streptolysin S (SLS) independently (9)(10)(11)(12). These findings point to a direct link between GAS carbohydrate metabolism and virulence factor production.…”
mentioning
confidence: 92%
See 1 more Smart Citation